HCI International 2020 -- Late breaking papers : universal access and inclusive design : 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020 proceedings /: universal access and inclusive design : 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020 proceedings. (2020) - Unknown
No abstract available